2019
DOI: 10.1108/jea-09-2019-227
|View full text |Cite
|
Sign up to set email alerts
|

The role of districts in supporting school leaders’ instructional leadership: a view and experience from a developing country

Abstract: The role of districts in supporting school leaders' instructional leadership: a view and experience from a developing country Introduction The downfall of Suharto's New Order regime in 1998 brought a fundamental change in the way Indonesia, the biggest country in South-East Asia spanning three time zones, was ruled. The Reform era started after the fall of the Suharto government in May 1998 and continued up until approximately a decade ago (Lindsey, 2018a, b). Nevertheless, the reforms are still underway.In fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…There is little empirical research on school development in Indonesia as compared to other Asian countries. Despite the plethora of studies over time on leadership practices elsewhere (Sumintono et al, 2019), more studies are highly needed on educational leadership and teacher development in Indonesia (Lumban Gaol, 2021; Pereira, 2016). A study by Dania and Andriani (2021) reported the challenges faced by school principals in public elementary schools in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…There is little empirical research on school development in Indonesia as compared to other Asian countries. Despite the plethora of studies over time on leadership practices elsewhere (Sumintono et al, 2019), more studies are highly needed on educational leadership and teacher development in Indonesia (Lumban Gaol, 2021; Pereira, 2016). A study by Dania and Andriani (2021) reported the challenges faced by school principals in public elementary schools in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment, pre-service professional development, selection, placement, additional study, evaluation, and succession planning are just some of the many policies and programmes that LaPointe et al (2006) say should accompany efforts to increase the professionalism of principals' leadership. Districts should make a concerted effort to shift the focus of principal leadership from Piter Joko Nugroho, Theo Jhoni Hartanto / Quality Profile of Remote Areas Elementary Schools merely focusing on school management to including cultivating instructional leadership (Sumintono et al, 2019). (Lee & Hallinger, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Enforcement of this policy is one of the strongest levers available to districts to improve the leadership quality of principals over time (Leithwood et al, 2019). In the context of supporting the development of principals' leadership, there must be a willingness from the district to change directions, in this case, the leadership of principals in schools in Indonesia does not only emphasize school management (Sumintono et al, 2019) but must be directed at leadership and leadership. instructional development (Lee & Hallinger, 2012).…”
Section: Recapitulation Of Quality Map Of Remote Area Elementary Schools Per Zonementioning
confidence: 99%
“…In the end, the effort to make changes returned to the education authorities in Kapuas and North Barito Regencies, Central Kalimantan Province, and other regions in Indonesia. To achieve the goal of improving the quality of schools (including in remote areas), as a developing country Indonesia through its district education leaders needs to borrow policies, followed by policy learning as stated (Lingard, 2010), adjusting to the context of schools in Indonesia (Sumintono et al, 2019). Policy lending needs to be pursued by translating or adapting it locally in the context of schools in Indonesia (Steiner-Khamsi, 2016).…”
Section: Recapitulation Of Quality Map Of Remote Area Elementary Schools Per Zonementioning
confidence: 99%
See 1 more Smart Citation